Syntheses, structures, luminescence and magnetic properties of seven isomorphous metal–organic frameworks based on 2, 7-bis(4-benzoic acid)-N-(4-benzoic acid)carbazole. (26th January 2018) - Chen, Dong-Hui; Lin, Ling; Sheng, Tian-Lu; Wen, Yue-Hong; Zhu, Xiao-Quan; Zhang, Lin-Tao; Hu, Sheng-Min; Fu, Rui-Biao; Wu, Xin-Tao
Abstract : Seven isomorphous lanthanide metal–organic frameworks with special luminescence and magnetic properties are synthesized and characterized. Abstract : We report herein seven novel lanthanide metal–organic frameworks (Ln-MOFs), [M (L27 )(DMA)(H2 O)·X H2 O] n (TCZ-M ), (M = Nd, Sm, Eu, Gd, Tb, Dy, Ho), (X = 2 or 3) (H3 L27 = 2, 7-bis(4-benzoic acid)- N -(4-benzoic acid)carbazole, DMA = N, N -dimethylacetamide, TCZ = "T"-shape carbazole-based MOFs, L27 = fully deprotonated H3 L27 3− ligand). X-ray crystallography showed that all theTCZ-M (M = Nd, Sm, Eu, Gd, Tb, Dy, Ho) are isomorphous and possess a 3, 6-connected three-dimensional (3D) framework with a point symbol of {4·6 2 }2 {4 2 ·6 10 ·8 3 }. The photoluminescence measurement indicates thatTCZ-Eu shows reddish-orange emission bands andTCZ-Sm shows both visible and near-infrared (NIR) emission bands. Magnetic susceptibility measurements show deviations from the Curie law mainly owing to the split of the ground term due to the ligand field and spin–orbit coupling inTCZ-Eu andTCZ-Sm . The magnetic properties ofTCZ-M (M = Nd, Gd, Tb, Dy, Ho) are also investigated, and the results indicate a ferromagnetic interaction between the Tb 3+ magnetic centers inTCZ-Tb and the antiferromagnetic interactions inTCZ-M (M = Nd, Gd, Dy, Ho).